2013
DOI: 10.1007/s10265-013-0576-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Arabidopsis thaliana MEKK1 via Ca2+ signaling as a part of the cold stress response

Abstract: The Arabidopsis mitogen activated protein kinase kinase kinase (MEKK1) plays an important role in stress signaling. However, little is known about the upstream pathways of MEKK1. This report describes the regulation of MEKK1 activity during cold signaling. Immunoprecipitated MEKK1 from cold-treated Arabidopsis seedlings showed elevated kinase activity towards mitogen activated protein kinase kinase2 (MKK2), one of the candidate MEKK1 substrates. To clarify how MEKK1 becomes active in response to cold stress si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 22 publications
3
65
0
Order By: Relevance
“…Under cold treatment, the phosphorylation levels of MPK3, MPK4, and MPK6 were significantly increased (Figure 1A), whereas the phosphorylation of MPK8 was significantly decreased (p-value<0.01) (Table S1). These results are consistent with previous studies (Furuya et al, 2013; Teige et al, 2004), which showed that MEKK1, MKK2, MPK4, and MPK6 are activated after cold treatment. Here, our method detected MPK3 as another MAPK responsive to cold conditions.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Under cold treatment, the phosphorylation levels of MPK3, MPK4, and MPK6 were significantly increased (Figure 1A), whereas the phosphorylation of MPK8 was significantly decreased (p-value<0.01) (Table S1). These results are consistent with previous studies (Furuya et al, 2013; Teige et al, 2004), which showed that MEKK1, MKK2, MPK4, and MPK6 are activated after cold treatment. Here, our method detected MPK3 as another MAPK responsive to cold conditions.…”
Section: Resultssupporting
confidence: 94%
“…In summary, previous studies reported that a MEKK1-MKK2-MPK4/MPK6 pathway is activated after cold treatment (Teige et al, 2004), and CRLK1, which is stimulated by binding to calmodulin and calcium, a second messenger in plants under cold stress, physically associates with and phosphorylates MEKK1 (Furuya et al, 2013; Yang et al, 2010a, 2010b). In this study, we found that MKK2 is the upstream kinase of MPK4 but not MPK3/6 in the cold signaling pathway.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations